Different responses of photosystem II and antioxidants to drought stress in two contrasting populations of Sour jujube from the Loess Plateau, China. Issue 6 (24th August 2016) - Wang, Yong; An, Yuyan; Yu, Jing; Zhou, Ziyun; He, Shaoxuan; Ru, Mei; Cui, Beimi; Zhang, Yu; Han, Ruilian; Liang, Zongsuo
Abstract: Sour jujube ( Zizyphus jujuba Mill. var. spinosus (Bge.) Hu) has gained considerable attention for its adaptation to drought prone environments. To characterize the physiological and biochemical basis of this drought adaptation, the effects of drought stress on Sour jujube seedlings were investigated in a greenhouse. Two contrasting populations were employed in our study, which were from the wet (YL) and dry (SB) climatic regions in the Loess Plateau of China. Results showed that SB exhibited lower water consumption and growth inhibition, but higher water use efficiency than YL under drought stress, indicating that growth of the wet‐climate population is more sensitive to drought stress. SB exhibited higher non‐photochemical quenching (NPQ) during progressive soil drying, higher photochemical quenching (qP) during the sustained water supply stage, and higher Δ F / F m ′ and qP during a re‐watering period than YL. These results further indicate that the dry‐climate population possesses better PSII efficiency under adverse conditions. YL showed larger increases in the production rate of superoxide anions, hydrogen peroxide, and hydroxyl radicals than SB during the progressive soil drying stage, indicating that SB suffered from less oxidative damage than YL. Antioxidant enzymes including catalase, ascorbate peroxidase, peroxidase and glutathione reductase, and antioxidants including carotenoids, flavonoids and proline; when these interact, they contribute greatly to the antioxidant capacity of the dry‐climate population. Taken together, the better photosynthetic potential and antioxidant capacity contribute to the better performance of Sour jujube from the dry‐climate, providing useful information for understanding the drought tolerance mechanisms of Sour jujube.